Gummo - Korine, Harmony; Sewell, Jacob; Sutton, Nick (Actor); Tosh, Lara (Burbank, CA : New Line Home Entertainment, 2001)
Never having recovered from a devastating tornado, an Ohio town's youth is directionless and amoral.
Features: animated photo gallery with audio commentary by director Harmony Korine, cast and crew filmographies.
Jacob Sewell, Nick Sutton, Lara Tosh, Jacob Reynolds, Darby Dougherty.
MPAA rating: R.
DVD, Dolby digital stereo.
Closed-captioned.
Keywords: Suburban life -- Ohio -- Drama; Video recordings for hard of hearing people; Feature films